2019
DOI: 10.1002/admi.201900942
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anticorrosion Property of Organic Coating Based on Liquid Metal

Abstract: properties, and low curing shrinkage, which can be simply modified or mixed with other additives to achieve different properties. [18][19][20][21][22][23][24][25][26] Some fillers with proper size and shape, such as clay, lamellar aluminum, and micaceous iron oxide particles, can improve the barrier properties of coatings. [1][2][3][4][5][6]10,11,27] However, these fillers or particles are solid particles, it is hard and time-consuming to obtain the smaller solid particles. In addition, the traditional solid f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…A growing number of researchers have tried to fabricate films by incorporating modified LM particles to coat matrices over the recent years, and these films tended to exhibit brilliant corrosion resistance and bacterial inhibition. For example, Zhang et al [ 116 ] incorporated Ga-based LM nanoparticles into epoxy-based coatings, and it was experimentally demonstrated that the films formed by this material exhibited an outstanding corrosion resistance. Simultaneously, the incorporation of LM particles amended the defects of the original coating and improved the mechanical properties of the film.…”
Section: Antibacterial Application Of Lm-based Materialsmentioning
confidence: 99%
“…A growing number of researchers have tried to fabricate films by incorporating modified LM particles to coat matrices over the recent years, and these films tended to exhibit brilliant corrosion resistance and bacterial inhibition. For example, Zhang et al [ 116 ] incorporated Ga-based LM nanoparticles into epoxy-based coatings, and it was experimentally demonstrated that the films formed by this material exhibited an outstanding corrosion resistance. Simultaneously, the incorporation of LM particles amended the defects of the original coating and improved the mechanical properties of the film.…”
Section: Antibacterial Application Of Lm-based Materialsmentioning
confidence: 99%
“…56 The reason why the corrosion resistance of epoxy coating was enhanced after adding LM and GO was that a small amount of LM particles had certain barrier properties, and the impermeability of GO to corrosive media also enhanced the corrosion resistance of the coating. 57,58 And it can be seen from Figure 10, after 15 days of 0.1 mol/L NaOH immersion, all coatings suffered less corrosion, and the surface remained in a similar state to that before immersion. After 15 days of immersion in 0.1 mol/L HCl, relatively large holes appeared on the surface of pure epoxy coating (Figure 10A), indicating that its surface had been corroded by acid.…”
Section: Mechanical Propertiesmentioning
confidence: 87%
“…The addition of LM and GO fillers kept the surface of the epoxy composite coatings relatively flat, indicating that LM and GO limited the further corrosion of HCl on the epoxy coating 56. The reason why the corrosion resistance of epoxy coating was enhanced after adding LM and GO was that a small amount of LM particles had certain barrier properties, and the impermeability of GO to corrosive media also enhanced the corrosion resistance of the coating 57,58. And it can be seen from Figure10, after 15 days of 0.1 mol/L NaOH immersion, all coatings suffered less…”
mentioning
confidence: 99%
“…16,17 Directly coating or filling the gaps between materials with LM can be used to achieve a uniform and controllable fusion of LM with the polymer matrix. [18][19][20] Furthermore, it is possible to regulate the properties of composite materials by introducing 2D material precursors onto the surface of LM through chemical deposition and utilizing LM as a reducing agent for interface reactions with the materials. 21,22 These methods all facilitate the effective integration of LM and 2D materials, offering pathways to construct composite materials with tailored properties and applications.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explored the incorporation of LM into materials through impregnation and vacuum filtration methods 16,17 . Directly coating or filling the gaps between materials with LM can be used to achieve a uniform and controllable fusion of LM with the polymer matrix 18–20 . Furthermore, it is possible to regulate the properties of composite materials by introducing 2D material precursors onto the surface of LM through chemical deposition and utilizing LM as a reducing agent for interface reactions with the materials 21,22 .…”
Section: Introductionmentioning
confidence: 99%